Attitudes towards dysmenorrhoea, impact and treatment seeking among adolescent girls: A rural school-based survey - Wong, Li Ping (Wiley, 2011)
Objective:  Study aimed to determine the prevalence of dysmenorrhoea, its impact, and treatment-seeking behaviour of rural adolescent girls in Malaysia. Participants and setting:  Large cross-sectional study on 1295 adolescent girls (aged 13-19 years) from 16 public secondary schools in rural districts of Kelantan, Malaysia conducted between February 2009 and April 2009. Results:  Dysmenorrhoea was reported in 76.0% of the participants. Concentration at school (59.9%) and participation in social events (58.6%) have been most affected. Multivariate analysis shows that being in upper secondary level was the strongest predictor for poor concentration, absenteeism, and poor school grade due to dysmenorrhoea. In spite of its high prevalence and enormous impact on their lives, 76.1% believed that dysmenorrhoea is a normal part of the female menstrual cycle and only 14.8% sought medical treatment. The majority of adolescents obtained information from their mothers (62.3%) and peers (52.9%). Conclusion:  The findings imply the need for educating adolescent girls on effective management of dysmenorrhoea. Education should be extended to parents and school peer leaders to address the reproductive health needs of adolescents.